Wear-resistant and anti-slip plastic tray and manufacturing method thereof
Through the combination of modified polyurethane acrylate and modified silica, the problem of poor filler compatibility in plastic tray coatings is solved, and the wear resistance and anti-slip performance and transparency are improved, ensuring the adhesion and aesthetics of the coating.
Patent Information
- Application Number
- CN202510574916.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-08-08
AI Technical Summary
In the wear-resistant and anti-slip coatings of existing plastic trays, the filler compatibility is poor, resulting in uneven dispersion, reduced adhesion, and reduced light transmittance, which affects aesthetics and performance.
Modified polyurethane acrylate and modified silica are used as substrates to react polytetrahydrofuran glycol, bihydroxyl-terminated polysiloxane with isophorone diisocyanate to form an isocyanate-terminated polyurethane prepolymer, and branching agent and diluent are added, coated on the tray matrix and cured under ultraviolet light.
It improves the wear resistance and transparency of the coating, enhances the adhesion between the coating and the tray substrate, and ensures the wear resistance and anti-slip performance and light transmittance of the plastic tray.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials and discloses a wear-resistant and anti-skid plastic pallet and a manufacturing method thereof. Background Art
[0002] Plastic pallets are widely used due to their advantages such as lightness, ease of processing, and recyclability. The wear and slip resistance of plastic pallets is an important indicator, so the pallet surface needs to be specially treated.
[0003] Polyurethane polyacrylate coatings offer excellent light transmittance and adhesion, making them a common choice for creating wear-resistant and non-slip coatings for pallet surfaces. However, their friction resistance needs to be improved, necessitating the addition of fillers such as quartz sand, corundum, silica, or rubber particles to increase surface roughness and achieve wear and slip resistance. However, fillers have poor compatibility in coating systems, leading to uneven dispersion and sedimentation, which compromises adhesion between the coating and the pallet substrate. Furthermore, excessive addition of fillers can result in a rough coating, reducing light transmittance and affecting aesthetics.
[0004] In summary, it is of great significance to study a wear-resistant and non-slip plastic pallet with good surface coating wear resistance, good bonding strength with the substrate, and good light transmittance and a manufacturing method thereof. Summary of the Invention
[0005] The object of the present invention is to provide a wear-resistant and non-slip plastic pallet and a manufacturing method thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solution: A method for manufacturing a wear-resistant and non-slip plastic pallet, comprising the following steps: S1: taking polytetramethylene glycol and dihydroxy-terminated polysiloxane, adding them to acetone and stirring evenly, heating to 65-70° C., adding isophorone diisocyanate and a tin catalyst (dibutyltin dilaurate), and stirring for 2-3 hours to obtain an isocyanate-terminated polyurethane prepolymer; adding a branching agent, reacting at 60-70° C. for 2-3 hours, adding hydroxyethyl methacrylate and stirring to react until the content of isocyanate groups in the system no longer changes, and removing the solvent by rotary evaporation to obtain a modified polyurethane acrylate;
[0007] S2: Take polyurethane acrylate JS-306, photoinitiator TPO, modified polyurethane acrylate, modified silica, and diluent, stir evenly to obtain a wear-resistant and anti-slip coating;
[0008] S3: Apply wear-resistant and anti-skid coating to the outer surface of the pallet base, 500mJ / cm 2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0009] More optimally, the tray base is made of PMMA.
[0010] More optimally, the modified polyurethane acrylate includes the following raw materials, calculated by mass: 15 to 20 parts of polytetramethylene glycol, 3 to 5 parts of dihydroxy-terminated polysiloxane, 20 to 30 parts of acetone, 25 to 30 parts of isophorone diisocyanate, 0.1 to 0.2 parts of tin catalyst, 5 to 8 parts of branching agent, and 10 to 15 parts of hydroxyethyl methacrylate.
[0011] More optimally, the wear-resistant and anti-slip coating includes the following raw materials, calculated by mass: 40 to 50 parts of polyurethane acrylate, 3 to 5 parts of photoinitiator, 20 to 30 parts of modified polyurethane acrylate, 10 to 15 parts of modified silica, and 100 to 120 parts of diluent.
[0012] More optimally, the branching agent includes trimethylolpropane and a modified branching agent in a mass ratio of (1-2): (4-6); the preparation of the modified branching agent includes the following steps: 1,2,4,5-tetrahydroxybenzene, 2-bromo-6-pyridineboronic acid pinacol, sodium carbonate, and tetrahydrofuran are uniformly mixed, stirred at 70-80°C for 5-7h, and the solvent is removed to obtain the modified branching agent.
[0013] More optimally, the modified branching agent includes the following raw materials, calculated by mass: 10 to 15 parts of 1,2,4,5-tetrahydroxybenzene, 25 to 30 parts of 2-bromo-6-pyridineboronic acid pinacol, 8 to 12 parts of sodium carbonate, and 80 to 120 parts of tetrahydrofuran.
[0014] More optimally, the preparation of the modified silica includes the following steps: under nitrogen protection, dispersing nano-silica in acetone, adding triethylene glycol monomethyl ether, pentaerythritol triacrylate, and glutaraldehyde, heating to 55-60° C. and stirring for reaction for 3-4 hours, removing the solvent, washing, and drying to obtain modified silica.
[0015] More optimally, the modified silicon dioxide comprises the following raw materials, calculated by mass: 5 to 10 parts of nano-silicon dioxide, 100 to 120 parts of acetone, 1 to 2 parts of triethylene glycol monomethyl ether, 3 to 5 parts of pentaerythritol triacrylate, and 10 to 15 parts of glutaraldehyde.
[0016] More optimally, the preparation method of nano-silica is: at room temperature (25-30°C), 30-40 parts of ethanol, 3-5 parts of ammonia water, and 2-5 parts of water are stirred evenly, and then 2-4 parts of ethyl orthosilicate are added thereto, stirred and reacted for 8-12 hours, aged, centrifuged, washed with water, and dried to obtain nano-silica.
[0017] More optimally, the preparation method of nano-silica is as follows: at 25°C, 35 parts of ethanol, 5 parts of 10% ammonia water (purchased from Nanjing Reagent, product number C0700130278), and 5 parts of water are stirred evenly, and then 4 parts of ethyl orthosilicate are added thereto, stirred for reaction for 12 hours, aged for 12 hours, centrifuged, washed with water, and dried to obtain nano-silica.
[0018] More optimally, the coating thickness of the wear-resistant and anti-slip coating is 20 to 30 μm.
[0019] More optimally, the diluent is acetone, butyl acetate, and propylene glycol methyl ether in a volume ratio of (5-6):1:(1-2).
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: a wear-resistant and anti-skid coating is applied to the outer surface of the pallet base to obtain a wear-resistant and anti-skid plastic pallet; the coating is based on polyurethane acrylate with good wear resistance and transparency, and silicon dioxide is added to further improve the wear resistance; because the addition of too much silicon dioxide will lead to a decrease in light transmittance, affecting the appearance of the pallet, but too little will lead to insufficient wear resistance and anti-skid performance, therefore, the present invention also introduces modified polyurethane acrylate: first, an isocyanate-terminated polyurethane prepolymer is prepared by polytetramethylene glycol, dihydroxy-terminated polysiloxane and an excess of isophorone diisocyanate; due to the introduction of polysiloxane chain segments, both wear resistance and toughness are improved. The wear resistance of the polyurethane prepolymer is improved, but the amount added should not be too much. Adding too much will cause a decrease in mechanical properties and transmittance due to compatibility and other problems. After the isocyanate-terminated polyurethane prepolymer is prepared, a branching agent is introduced. The branching agent is trimethylolpropane and a modified branching agent in a mass ratio of (1-2): (4-6). The modified branching agent is 1,2,4,5-tetrahydroxybenzene modified with 2-bromo-6-pyridineboronic acid pinacol. The introduction of borate groups and benzene rings further improves the wear resistance. However, the amount of the modified branching agent introduced should not be too much, because the presence of the benzene ring will lead to a decrease in transparency and easy yellowing. Therefore, trimethylolpropane is also introduced to improve the branching rate while ensuring transparency and wear resistance.
[0021] The present invention uses silica modified with triethylene glycol monomethyl ether and pentaerythritol triacrylate. The ether structure of triethylene glycol monomethyl ether helps improve wettability and adhesion between the coating and the pallet substrate. Pentaerythritol triacrylate acts as a diluent and participates in the curing reaction, thereby improving the performance and curing rate of the coating.
[0022] The present invention also selects acetone, butyl acetate, and propylene glycol methyl ether in a volume ratio of 5:1:1 as diluents, taking into account solubility and volatility, and at the same time controlling the thickness to 20 to 30 μm. After curing under ultraviolet light, a coating with good wear resistance, anti-slip properties, and good light transmittance is obtained, thereby producing a high-quality wear-resistant and anti-slip plastic pallet. DETAILED DESCRIPTION
[0023] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0024] It should be noted that the purchasers of all raw materials involved in the present invention are not particularly restricted, and illustratively include: ethanol (CAS: 64-17-5); polyurethane acrylate (JS-306, Hunan Jinhai Technology Co., Ltd.); photoinitiator TPO (CAS: 75980-60-8); acetone (CAS: 67-64-1); butyl acetate (CAS: 123-86-4); propylene glycol methyl ether (CAS: 107-98-2); ammonia water (10%, Nanjing reagent C0700130278); tetraethyl orthosilicate (CAS: 78-10-4); triethylene glycol monomethyl ether (CAS: 112-35-6); pentaerythritol triacrylate (CAS: 3524-68-3); glutaraldehyde (CAS: 111-30-8); polytetramethylene glycol (PTMG-1000, Mn=1000); bis-hydroxy-terminated polysiloxane (Shanghai Yuanye T22990); isophorone diisocyanate (CAS: 4098-71-9); dibutyltin dilaurate (CAS: 77-58-7); trimethylolpropane (CAS: 77-99-6); hydroxyethyl methacrylate (CAS: 868-77-9); sodium carbonate (anhydrous sodium carbonate, CAS: 497-19-8);
[0025] Unless otherwise specified, the following are parts by mass and mass ratios;
[0026] The preparation method of nano-silica is as follows: 35 parts of ethanol, 5 parts of ammonia water and 5 parts of water are stirred uniformly at 25°C, 4 parts of ethyl orthosilicate are added thereto, stirred for reaction for 12 hours, aged for 12 hours, centrifuged, washed with water and dried to obtain nano-silica;
[0027] The diluent is acetone, butyl acetate, and propylene glycol methyl ether in a volume ratio of 5:1:1;
[0028] Example 1: S1: Under nitrogen protection, 8 parts of nano-silica were dispersed in 100 parts of acetone, 1 part of triethylene glycol monomethyl ether, 4 parts of pentaerythritol triacrylate, and 14 parts of glutaraldehyde were added, the temperature was raised to 60°C and stirred for reaction for 4 hours, the solvent was removed, the mixture was washed, and dried to obtain modified silica;
[0029] S2: 14 parts of 1,2,4,5-tetrahydroxybenzene, 28 parts of 2-bromo-6-pyridineboronic acid pinacol, 10 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0030] S3: 18 parts of polytetramethylene glycol and 4 parts of dihydroxy-terminated polysiloxane were added to 25 parts of acetone and stirred to disperse uniformly. The mixture was heated to 70° C., 30 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate were added, and the mixture was stirred for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer. 1 part of trimethylolpropane and 5 parts of a modifying branching agent were added, and the mixture was reacted at 65° C. for 3 hours. 14 parts of hydroxyethyl methacrylate was added and the reaction was continued with stirring. The isocyanate group content of the system was determined to be no longer changed by toluene-di-n-butylamine titration method, and the reaction was stopped. The solvent was removed by rotary evaporation to obtain a modified polyurethane acrylate.
[0031] S4: Take 45 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 25 parts of modified polyurethane acrylate, 12 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-skid coating, and apply the wear-resistant and anti-skid coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm 2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0032] Example 2: S1: Under nitrogen protection, 5 parts of nano-silica were dispersed in 100 parts of acetone, 1 part of triethylene glycol monomethyl ether, 3 parts of pentaerythritol triacrylate, and 10 parts of glutaraldehyde were added, the temperature was raised to 60°C and stirred for reaction for 4 hours, the solvent was removed, the mixture was washed, and dried to obtain modified silica;
[0033] S2: 10 parts of 1,2,4,5-tetrahydroxybenzene, 25 parts of 2-bromo-6-pyridineboronic acid pinacol, 8 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0034] S3: 15 parts of polytetramethylene glycol and 3 parts of dihydroxy-terminated polysiloxane were added to 25 parts of acetone and stirred to disperse uniformly. The mixture was heated to 70° C., 25 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate were added, and the mixture was stirred for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer. 1 part of trimethylolpropane and 4 parts of a modifying branching agent were added, and the mixture was reacted at 65° C. for 3 hours. 10 parts of hydroxyethyl methacrylate were added and the reaction was continued with stirring. The isocyanate group content of the system was determined to be no longer changed by toluene-di-n-butylamine titration method, and the reaction was stopped. The solvent was removed by rotary evaporation to obtain a modified polyurethane acrylate.
[0035] S4: Take 40 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 30 parts of modified polyurethane acrylate, 10 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-skid coating, and apply the wear-resistant and anti-skid coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm 2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0036] Example 3: S1: Under nitrogen protection, 10 parts of nano-silica were dispersed in 100 parts of acetone, 2 parts of triethylene glycol monomethyl ether, 5 parts of pentaerythritol triacrylate, and 15 parts of glutaraldehyde were added, the temperature was raised to 60°C and stirred for reaction for 4 hours, the solvent was removed, the mixture was washed, and dried to obtain modified silica;
[0037] S2: 15 parts of 1,2,4,5-tetrahydroxybenzene, 30 parts of 2-bromo-6-pyridineboronic acid pinacol, 12 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0038] S3: Take 20 parts of polytetramethylene glycol and 5 parts of dihydroxy-terminated polysiloxane, add 25 parts of acetone, stir and disperse evenly, raise the temperature to 70°C, add 30 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate, and stir for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer; add 2 parts of trimethylolpropane and 6 parts of a modifying branching agent, react at 65°C for 3 hours, add 15 parts of hydroxyethyl methacrylate and continue stirring to react. The isocyanate group content of the system is no longer changed as determined by toluene-di-n-butylamine titration method, and the reaction is stopped; the solvent is removed by rotary evaporation to obtain a modified polyurethane acrylate;
[0039] S4: Take 50 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 20 parts of modified polyurethane acrylate, 15 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-skid coating, and apply the wear-resistant and anti-skid coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm 2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0040] Example 4: S1: Under nitrogen protection, 10 parts of nano-silica were dispersed in 100 parts of acetone, 2 parts of triethylene glycol monomethyl ether, 5 parts of pentaerythritol triacrylate, and 15 parts of glutaraldehyde were added, the temperature was raised to 60°C and stirred for reaction for 4 hours, the solvent was removed, the mixture was washed, and dried to obtain modified silica;
[0041] S2: 10 parts of 1,2,4,5-tetrahydroxybenzene, 25 parts of 2-bromo-6-pyridineboronic acid pinacol, 8 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0042] S3: 15 parts of polytetramethylene glycol and 3 parts of dihydroxy-terminated polysiloxane were added to 25 parts of acetone and stirred to disperse uniformly. The mixture was heated to 70° C., 25 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate were added, and the mixture was stirred for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer. 1 part of trimethylolpropane and 4 parts of a modifying branching agent were added, and the mixture was reacted at 65° C. for 3 hours. 15 parts of hydroxyethyl methacrylate was added and the reaction was continued with stirring. The isocyanate group content of the system was determined to be no longer changed by toluene-di-n-butylamine titration method, and the reaction was stopped. The solvent was removed by rotary evaporation to obtain a modified polyurethane acrylate.
[0043] S4: Take 45 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 25 parts of modified polyurethane acrylate, 10 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-slip coating, and apply the wear-resistant and anti-slip coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm 2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0044] Comparative Example 1 (changing the mass ratio of each raw material in the wear-resistant and anti-slip coating, and the remaining method steps are consistent with Example 1): S1: Under nitrogen protection, 8 parts of nano-silica were dispersed in 100 parts of acetone, 1 part of triethylene glycol monomethyl ether, 4 parts of pentaerythritol triacrylate, and 14 parts of glutaraldehyde were added, and the temperature was raised to 60°C and stirred for 4 hours. The solvent was removed, washed, and dried to obtain modified silica;
[0045] S2: 14 parts of 1,2,4,5-tetrahydroxybenzene, 28 parts of 2-bromo-6-pyridineboronic acid pinacol, 10 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0046] S3: 18 parts of polytetramethylene glycol and 4 parts of dihydroxy-terminated polysiloxane were added to 25 parts of acetone and stirred to disperse uniformly. The mixture was heated to 70° C., 30 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate were added, and the mixture was stirred for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer. 1 part of trimethylolpropane and 5 parts of a modifying branching agent were added, and the mixture was reacted at 65° C. for 3 hours. 14 parts of hydroxyethyl methacrylate was added and the reaction was continued with stirring. The isocyanate group content of the system was determined to be no longer changed by toluene-di-n-butylamine titration method, and the reaction was stopped. The solvent was removed by rotary evaporation to obtain a modified polyurethane acrylate.
[0047] S4: Take 45 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 15 parts of modified polyurethane acrylate, 20 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-skid coating, and apply the wear-resistant and anti-skid coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0048] Comparative Example 2 (changing the mass ratio of each raw material in the wear-resistant and anti-slip coating, and the remaining method steps are consistent with Example 1): S1: Under nitrogen protection, 8 parts of nano-silica were dispersed in 100 parts of acetone, 1 part of triethylene glycol monomethyl ether, 4 parts of pentaerythritol triacrylate, and 14 parts of glutaraldehyde were added, and the temperature was raised to 60°C and stirred for 4 hours. The solvent was removed, washed, and dried to obtain modified silica;
[0049] S2: 14 parts of 1,2,4,5-tetrahydroxybenzene, 28 parts of 2-bromo-6-pyridineboronic acid pinacol, 10 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0050] S3: 18 parts of polytetramethylene glycol and 4 parts of dihydroxy-terminated polysiloxane were added to 25 parts of acetone and stirred to disperse uniformly. The mixture was heated to 70° C., 30 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate were added, and the mixture was stirred for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer. 1 part of trimethylolpropane and 5 parts of a modifying branching agent were added, and the mixture was reacted at 65° C. for 3 hours. 14 parts of hydroxyethyl methacrylate was added and the reaction was continued with stirring. The isocyanate group content of the system was determined to be no longer changed by toluene-di-n-butylamine titration method, and the reaction was stopped. The solvent was removed by rotary evaporation to obtain a modified polyurethane acrylate.
[0051] S4: Take 45 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 35 parts of modified polyurethane acrylate, 5 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-skid coating, and apply the wear-resistant and anti-skid coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm 2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0052] Comparative Example 3 (increasing the amount of the modified branching agent, and the remaining steps are consistent with Example 1): S1: Under nitrogen protection, 8 parts of nano-silica were dispersed in 100 parts of acetone, 1 part of triethylene glycol monomethyl ether, 4 parts of pentaerythritol triacrylate, and 14 parts of glutaraldehyde were added, and the temperature was raised to 60° C. and stirred for 4 hours. The solvent was removed, washed, and dried to obtain modified silica;
[0053] S2: 14 parts of 1,2,4,5-tetrahydroxybenzene, 28 parts of 2-bromo-6-pyridineboronic acid pinacol, 10 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0054] S3: 18 parts of polytetramethylene glycol and 4 parts of dihydroxy-terminated polysiloxane were added to 25 parts of acetone and stirred to disperse uniformly. The mixture was heated to 70° C., 30 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate were added, and the mixture was stirred for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer. 8 parts of a modifying branching agent were added, and the mixture was reacted at 65° C. for 3 hours. 14 parts of hydroxyethyl methacrylate were added and the reaction was continued with stirring. The isocyanate group content of the system was determined to be no longer changed by toluene-di-n-butylamine titration method, and the reaction was stopped. The solvent was removed by rotary evaporation to obtain a modified polyurethane acrylate.
[0055] S4: Take 45 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 25 parts of modified polyurethane acrylate, 12 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-skid coating, and apply the wear-resistant and anti-skid coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm 2 Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0056] Comparative Example 4 (changing the amount of polytetrahydrofuran diol and dihydroxy-terminated polysiloxane added, the remaining method steps are consistent with Example 1): S1: Under nitrogen protection, 8 parts of nano-silica are dispersed in 100 parts of acetone, 1 part of triethylene glycol monomethyl ether, 4 parts of pentaerythritol triacrylate, and 14 parts of glutaraldehyde are added, the temperature is raised to 60° C. and stirred for reaction for 4 hours, the solvent is removed, the mixture is washed, and dried to obtain modified silica;
[0057] S2: 14 parts of 1,2,4,5-tetrahydroxybenzene, 28 parts of 2-bromo-6-pyridineboronic acid pinacol, 10 parts of sodium carbonate, and 100 parts of tetrahydrofuran were mixed uniformly, stirred at 75°C for 6 hours, and the solvent was removed to obtain a modified branching agent;
[0058] S3: Take 12 parts of polytetramethylene glycol and 8 parts of dihydroxy-terminated polysiloxane, add 25 parts of acetone, stir and disperse evenly, raise the temperature to 70°C, add 30 parts of isophorone diisocyanate and 0.1 parts of dibutyltin dilaurate, and stir for 3 hours to obtain an isocyanate-terminated polyurethane prepolymer; add 1 part of trimethylolpropane and 5 parts of a modifying branching agent, react at 65°C for 3 hours, add 14 parts of hydroxyethyl methacrylate and continue stirring to react. The isocyanate group content of the system is no longer changed as determined by toluene-di-n-butylamine titration method, and the reaction is stopped; the solvent is removed by rotary evaporation to obtain a modified polyurethane acrylate;
[0059] S4: Take 45 parts of polyurethane acrylate JS-306, 3 parts of photoinitiator TPO, 25 parts of modified polyurethane acrylate, 12 parts of modified silica, and 100 parts of diluent, stir evenly to obtain a wear-resistant and anti-skid coating, and apply the wear-resistant and anti-skid coating to the outer surface of the pallet substrate with a coating thickness of 30 μm and a spray rate of 500 mJ / cm 2Cured under ultraviolet light, a wear-resistant and non-slip plastic tray is obtained.
[0060] Performance test: The wear-resistant and anti-skid coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were sprayed on the PMMA plate with a thickness of 30 μm, leveled in a 50°C oven for 5 minutes, and then irradiated with an energy of 500 mJ / cm 2 The sample was cured under ultraviolet light to obtain a sample; (1) the mass loss after 100 revolutions of wear was tested using a JM-IV abrasion tester and a rotating friction rubber wheel method; (2) the transmittance was tested on an optical transmittance meter, with wavelength requirements of 550nm / 380nm; see Table 1 for details;
[0061] Table 1:
[0062] Mass loss / g Transmittance / % Example 1 0.044 96.0 Example 2 0.045 95.8 Example 3 0.046 95.9 Example 4 0.044 95.6 Comparative Example 1 0.045 82.5 Comparative Example 2 0.053 89.2 Comparative Example 3 0.050 88.7 Comparative Example 4 0.049 85.1
[0063] Conclusion: In Comparative Example 1, the mass ratio of raw materials in the wear-resistant and anti-skid coating was changed, and the amount of modified silica was increased, which had a significant effect on the transparency; in Comparative Example 2, the amount of modified polyurethane acrylate was increased and the amount of modified silica was reduced, and the performance was also not as good as that in the embodiment, which shows that the control of the amount of addition is of great significance; in Comparative Example 3, the amount of modified branching agent was increased, and the performance decreased significantly; in Comparative Example 4, the addition ratio of polytetramethylene glycol and dihydroxy-terminated polysiloxane was changed, and the transparency decreased significantly due to compatibility and other issues; in summary, the wear-resistant and anti-skid coating prepared by the present invention has good wear resistance and high transparency, and can be used to prepare wear-resistant and anti-skid plastic pallets.
[0064] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A method for manufacturing a wear-resistant and non-slip plastic pallet, characterized by: The following steps are involved: S1: Take polytetramethylene glycol and dihydroxy-terminated polysiloxane, add them to acetone and stir evenly, raise the temperature to 65-70°C, add isophorone diisocyanate and tin catalyst, and stir for 2-3 hours to obtain an isocyanate-terminated polyurethane prepolymer; add a branching agent, react at 60-70°C for 2-3 hours, add hydroxyethyl methacrylate and stir until the content of isocyanate groups in the system no longer changes, and remove the solvent by rotary evaporation to obtain a modified polyurethane acrylate; S2: Take polyurethane acrylate, photoinitiator, modified polyurethane acrylate, modified silica, and diluent, stir evenly, and obtain a wear-resistant and anti-slip coating; S3: applying a wear-resistant and anti-skid coating to the outer surface of the pallet base and curing the coating to obtain a wear-resistant and anti-skid plastic pallet.
2. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 1, characterized in that: The modified polyurethane acrylate comprises the following raw materials, calculated by mass: 15 to 20 parts of polytetramethylene glycol, 3 to 5 parts of dihydroxy-terminated polysiloxane, 20 to 30 parts of acetone, 25 to 30 parts of isophorone diisocyanate, 0.1 to 0.2 parts of tin catalyst, 5 to 8 parts of branching agent, and 10 to 15 parts of hydroxyethyl methacrylate.
3. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 1, characterized in that: The wear-resistant and anti-skid coating comprises the following raw materials, calculated by mass: 40 to 50 parts of polyurethane acrylate, 3 to 5 parts of photoinitiator, 20 to 30 parts of modified polyurethane acrylate, 10 to 15 parts of modified silicon dioxide, and 100 to 120 parts of diluent.
4. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 1, characterized in that: The branching agent comprises trimethylolpropane and a modified branching agent in a mass ratio of (1-2):(4-6); the preparation of the modified branching agent comprises the following steps: uniformly mixing 1,2,4,5-tetrahydroxybenzene, 2-bromo-6-pyridineboronic acid pinacol, sodium carbonate, and tetrahydrofuran, stirring at 70-80° C. for 5-7 hours, and removing the solvent to obtain the modified branching agent.
5. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 4, characterized in that: The modified branching agent includes the following raw materials, calculated by mass: 10 to 15 parts of 1,2,4,5-tetrahydroxybenzene, 25 to 30 parts of 2-bromo-6-pyridineboronic acid pinacol, 8 to 12 parts of sodium carbonate, and 80 to 120 parts of tetrahydrofuran.
6. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 1, characterized in that: The preparation of the modified silicon dioxide comprises the following steps: Under nitrogen protection, nano-silica was dispersed in acetone, triethylene glycol monomethyl ether, pentaerythritol triacrylate and glutaraldehyde were added, the temperature was raised to 55-60°C and stirred for reaction for 3-4 hours, the solvent was removed, washed and dried to obtain modified silica.
7. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 6, characterized in that: The modified silicon dioxide comprises the following raw materials, calculated by mass: 5 to 10 parts of nano silicon dioxide, 100 to 120 parts of acetone, 1 to 2 parts of triethylene glycol monomethyl ether, 3 to 5 parts of pentaerythritol triacrylate, and 10 to 15 parts of glutaraldehyde.
8. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 1, characterized in that: The coating thickness of the wear-resistant and anti-slip coating is 20 to 30 μm.
9. The method for manufacturing a wear-resistant and non-slip plastic pallet according to claim 1, characterized in that: The diluent is acetone, butyl acetate and propylene glycol methyl ether in a volume ratio of (5-6):1:(1-2).
10. A plastic pallet prepared according to the method for manufacturing a wear-resistant and non-slip plastic pallet according to any one of claims 1 to 9.
Citation Information
Cited By
High-strength coating, preparation method and application in SMC (Sheet Molding Compound)
CN121022243A
High-strength coating, method of preparation and application on SMC
CN121022243B